The Difference of allergic reaction on hand sanitizer gel and liquid among nurses at RSU Karsa Husada Batu - Adilah, Lilah (University of Muhammadiyah Malang, 2023)
Introduction: The program to improve the hand hygiene of health workers has been declared by WHO through a patient safety program that sparked the Global Patient Safety Challenge